17q25 Locus is associated with white matter hyperintensity volume in ischemic stroke, but not with lacunar stroke status. - Adib-Samii, P; Rost, N; Traylor, M; Devan, W; Biffi, A; Lanfranconi, S; Fitzpatrick, K; Bevan, S; Kanakis, A; Valant, V; Gschwendtner, A; Malik, R; et al. (2013)
BACKGROUND AND PURPOSE: Recently, a novel locus at 17q25 was associated with white matter hyperintensities (WMH) on MRI in stroke-free individuals. We aimed to replicate the association with WMH volume (WMHV) in patients with ischemic stroke. If the association acts by promoting a small vessel arteriopathy, it might be expected to also associate with lacunar stroke. METHODS: We quantified WMH on MRI in the stroke-free hemisphere of 2588 ischemic stroke cases. Association between WMHV and 6 single-nucleotide polymorphisms at chromosome 17q25 was assessed by linear regression. These single-nucleotide polymorphisms were also investigated for association with lacunar stroke in 1854 cases and 51 939 stroke-free controls from METASTROKE. Meta-analyses with previous reports and a genetic risk score approach were applied to identify other novel WMHV risk variants and uncover shared genetic contributions to WMHV in community participants without stroke and ischemic stroke. RESULTS: Single-nucleotide polymorphisms at 17q25 were associated with WMHV in ischemic stroke, the most significant being rs9894383 (P=0.0006). In contrast, there was no association between any single-nucleotide polymorphism and lacunar stroke. A genetic risk score analysis revealed further genetic components to WMHV shared between community participants without stroke and ischemic stroke. CONCLUSIONS: This study provides support for an association between the 17q25 locus and WMH. In contrast, it is not associated with lacunar stroke, suggesting that the association does not act by promoting small-vessel arteriopathy or the same arteriopathy responsible for lacunar infarction.